Parasacral Perforator Flaps for Reconstruction of Sacral Pressure Sores. Issue 1 (July 2015) - Lin, Chin-Ta; Chen, Shih-Yi; Chen, Shyi-Gen; Tzeng, Yuan-Sheng; Chang, Shun-Cheng
Abstract : Background: Despite advances in reconstruction techniques, pressure sores continue to present a challenge to the plastic surgeon. The parasacral perforator flap is a reliable flap that preserves the entire contralateral side as a future donor site. On the ipsilateral side, the gluteal muscle itself is preserved and all flaps based on the inferior gluteal artery are still possible. We present our experience of using parasacral perforator flaps in reconstructing sacral defects. Methods: Between August 2004 and January 2013, 19 patients with sacral defects were included in this study. All the patients had undergone surgical reconstruction of sacral defects with a parasacral perforator flap. The patients' sex, age, cause of sacral defect, flap size, flap type, numbers of perforators used, rotation angle, postoperative complications, and hospital stay were recorded. Results: There were 19 parasacral perforator flaps in this series. All flaps survived uneventfully except for 1 parasacral perforator flap, which failed because of methicillin-resistant Staphylococcus aureus infection. The overall flap survival rate was 95% (18/19). The mean follow-up period was 17.3 months (range, 2–24 months). The average length of hospital stay was 20.7 days (range, 9–48 days). No flap surgery-related mortality was found. Also, there was no recurrence of sacral pressure sores or infected pilonidal cysts during the follow-up period. Conclusions: Perforator-based flaps have become popular in modern reconstructive surgery because of low donor-site morbidity and good preservation of muscle. Parasacral perforator flaps are durable and reliable in reconstructing sacral defects. We recommend the parasacral perforator flap as a good choice for reconstructing sacral defects.